Associação entre provável bruxismo em vigília e bullying entre escolares - Letícia Silva Alonso (2019)
Bruxism is a behavior characterized by the grinding and/or clenching of teeth that is strongly associated with emotional factors. Bullying can affect the student emotionally. The objective of this study was to evaluate the association between probable awake bruxism (PAB) and bullying among schoolchildren. A representative cross-sectional study was conducted in Lavras, Minas Gerais, Brazil. This study was submitted to the Ethics and Research Committee on Human Beings of the Federal University of Minas Gerais (COEP/UFMG) and approved (CAAE 82839718.4.0000.5149). Prior to the main study, a pilot study was conducted with 45 students from a public school in Lavras. Participated in the study schoolchildren aged 8 to 11 years, enrolled in public and private schools, and their parents/caregivers. The parents/caregivers answered a questionnaire with sociodemographic questions and characteristic of their children’s/adolescents’ sleep. The students answered two questionnaires, one with questions about the history of muscular pain, headache, triggers factors of bullying and the occurrence of awake bruxism and the the Brazilian version of the Olweus Bully/Victim Questionnaire (OBVQ) to determine the students who could be involved in bullying. An extra and intraoral clinical analysis was performed by one examiner to identify clinical signs such as: linea alba and indentations on the tongue, palpation pain in the masseter and temporalis muscles and tooth wear by attrition. A training and calibration for the evaluation of attrition tooth wear was performed. The PAB was measured on a scale based on the frequency of self-reported awake bruxism by child/adolescent and on the number of clinical signs and symptoms, where a larger score represented a greater PAB severity. The PAB was categorized as mild, moderate or severe according to the report and the number of symptoms and clinical signs present in the dental evaluation. Statistical analysis included descriptive analysis, Mann-Whitney test (p <0.05) and Poisson regression (p <0.05). A total of 434 students participated in the study. The percentage of children/adolescents regarding sex was similar, with a slightly higher value for the females (51.8%). The total prevalence of PBV was 43.7%, categorized as probable mild bruxism awake (35.7%), probable moderate bruxism awake (7.8%) and probable severe bruxism awake (0.2%). In the bivariate analysis, there was an association between the characteristics of the teeth as triggers of bullying (p = 0.012) and other characteristics (such as bad breath, squint, ear, among others) (p = 0.006) and the PAB score. Victims of bullying (PR=1.85, 95%CI=1.37-2.50, p<0.001) and victim-aggressors (PR=1.76, 95%CI=1.14-2.72, p=0.010) presented higher PAB severity than students who were not involved in bullying. Schoolchildren who wake up tired in the morning at least once a week presented higher PAB severity than those who did not report tiredness (PR=1.36, 95%CI=1.03-1.79, p=0.026). This study concluded that schoolchildren who reported that their teeth were triggers of bullying were significantly associated with the PAB; schoolchildren who are victims of bullying and victim-aggressors had a higher prevalence of higher severity of PAB, as well as those schoolchildren who reported fatigue upon waking